Effects of Fungal Pancreatic Enzymes on the Function of Islet Cells in Syrian Golden Hamsters - Nozawa, Fumiaki; Yalniz, Mehmet; Saruc, Murat; Standop, Jens; Egami, Hiroshi; Pour, Parviz M (JOP. Journal of the Pancreas, 2013)
Context Our previous studies showed that porcine pancreatic enzymes in Syrian golden hamsters with peripheral insulin resistance normalizes the plasma insulin level, reduces the size of enlarged islets and inhibits the increased DNA synthesis in the beta-cell of islets. Objective In order to exclude the possibility that these effects was attributed to some contaminants of this crude material, we tested the effect of purified fungal pancreatic enzyme (FPE) that contains primarily amylase and lipase without (FPE) and with addition of chymotrypsin (FPE+chy). Material and methods In a pilot study we tested the effect of different doses of FPE given in drinking water on insulin level, islet size and DNA synthesis of islet cells in hamsters with induced peripheral insulin resistance by a high fat diet. The most effective dose of FPE on these parameters was used in a long-term experiment with FPE and FPE+chy in hamsters fed a high-fat diet for 36 or 40 weeks. Results In the pilot study a dose of 2 g/kg body weight was found to be optimal for controlling the body weight, normalizing plasma insulin level, the size of islets, the DNA synthesis and the number of insulin cells in the islets. These data were produced in the long-term study, where steatorrhea was also inhibited. Addition of chymotrypsin had no effects on these parameters. Conclusion Pancreatic lipase and amylase appear to be responsible for the observed effects and offer a safe and effective natural product for the treatment of pancreatic diseases, including acute pancreatitis, chronic pancreatic, cystic fibrosis and any conditions associated with peripheral insulin resistance, including obesity and type 2 diabetes. The possible mechanism of the action is discussed. Image: In the fungal pancreatic enzyme-treated group, 25% of the cells react with anti-glucagon (blue) and 10% with anti-somatostatin antibody (brown).